Towards a Housing Preservation Culture - Uta Pottgiesser; Wido Quist (Docomomo Journal, 2023)
After the two 2022-issues of the Docomomo Journal, number 66 on ‘Modern Plastic Heritage’ and number 67 on ‘Multiple Modernisms in Ukraine,’ this issue reveals another chapter of an often and diversely described theme of Modern Movement and a pressing subject worldwide: Housing.